Active Layer Thickness and Permafrost Area Projections for the 21st Century - Peng, Xiaoqing; Zhang, Tingjun; Frauenfeld, Oliver W.; Mu, Cuicui; Wang, Kang; Wu, Xiaodong; Guo, Donglin; Luo, Jing; Hjort, Jan; Aalto, Juha; Karjalainen, Olli; Luoto, Miska (John Wiley & Sons, 2023)
Permafrost warming leads to greenhouse gas release to the atmosphere, resulting in a positive feedback to climate change. Earth system models indicate that more than 80% of the near-surface permafrost is projected to disappear by the end of this century, but with a high degree of uncertainty. Here, we apply the Stefan solution to estimate permafrost degradation under future emission scenarios. We find that the most severe future scenario is likely to lead to only a 14% decrease in area extent of the near-surface permafrost at 3.5 m depth, and an area extent decrease of 1.3% at a depth of 6.0 m. Relative to active layer thickness increases from historical simulations, we find a less than 30% deepening for most permafrost regions by the end of this century. These results imply that the Stefan solution provides near-surface permafrost area extent degradation estimates that are substantially lower than directly projected by models.